New Trends in Allergy IV Together with Environmental Allergy and Allergotoxicology III - Ring, Johannes; Behrendt, Heidrun; Vieluf, Dieter (Springer Berlin Heidelberg, 1997)
There is no doubt among experts that the prevalence of allergic diseases has increased in many industrialized countries in recent years. The rea sons for this increase are unknown; only suppositions exist. Many people focus on environmental influences. However, the assumption that air pollution alone is responsible for this increase seems to be too simple: many other influences, including the genetic predisposition of individual patients, allergen exposure, and possibly socioeconomic factors, also have to be taken into consideration. Although our understanding of the complex mechanisms of allergic diseases has considerably improved thanks to the progress made in ex perimental immunology and allergology, we still have a long way to go before this scientific knowledge is translated into new therapeutic mo dalities. For this reason, the scientific community welcomed the gathering of scientists from very different disciplines and different parts of the world at an international symposium, "New Trends in Allergy IV" together with "Environmental Allergy and Allergotoxicology III" in Hamburg in 1995. This volume contains the invited papers, covering a wide range from basic science to practical clinical diagnosis and therapy. A further unique feature of this event was the concomitant first official workshop of the Environmental Pollution and Allergy Committee of the International Association of Allergy and Clinical Immunology (IAACI), at which the state of scientific knowledge in this field was defined and formulated
Keywords: Dermatology; Allergology; Immunology; Allergy; Umweltkrankheit; Allergie; Konferenzschrift -- 1995 -- Hamburg; Konferenzschrift